Network analysis for GPS UTMnav system: preliminary stage - A. Majid, Siti Nuruljannah; Musa, Tajul Ariffin; Setan, Halim; Musliman, Ivin Amri (2008)
This ongoing research concentrates on the network analysis of the existing UTM navigation system (UTMnav). The aim is to overcome the limitation of UTMnav system in network analysis. A few shortest-path algorithms have been studied namely Dijkstra's, Floyd Warshall and A-Star (A*). Each algorithm was reviewed and a simulation test was conducted to evaluate the selected algorithms. The simulation test was conducted using Visual Basic (VB) environment. A database of the selected network is created using MapInfo Professional and AutoCAD Map software. The understanding of the simulation test will motivate this research to improve on the UTMnav network analysis.